Water Safety and Backflow Prevention. - Novak, Celeste Allen (Architectural Record, 2020)
Informed design professionals who understand the basics of backflow prevention are able to successfully manage regulations and safely deliver fresh drinking water in their projects. DEGREES OF HAZARD Backflow into the public water distribution system can be prevented by eliminating cross-connections or adding backflow preventers. PREVENTABLE BACKFLOW FAILURES Public health officials have documented numerous incidents of unprotected cross-connections resulting in backflow. The key elements to a cross-connection control program include the isolation of the domestic water supply and containment at the meter, resulting in total backflow protection through the use of backflow preventers.